2017
DOI: 10.33233/fb.v18i3.1067
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do Kinesio Taping sobre o edema linfático

Abstract: Introdução: O linfedema é caracterizado pelo acúmulo excessivo e persistente de fluidos e proteínas nos espaços intersticiais pela incompetência do sistema linfático. Acredita-se que a propriedade elástica da bandagem promove tensões e trações superficiais na pele capazes de drenar os fluidos corporais. Objetivo: Esta revisão sistemática se propôs a investigar os efeitos da Kinesio Taping (KT) sobre o edema linfático. Método: Pesquisa do tipo exploratório-documental com abordagem quantitativa, cujas bases de d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Kinesio taping has been used as an innovative resource in the treatment of lymphedema, as it can drain body fluids. Pivetta et al, 20 reported a significant reduction of lymphedema in groups that used Kinesio taping either alone or in association with other techniques. High-voltage stimulation may increase venous blood flow and edema absorption, since negative polarity has sufficient intensity to provide muscle contractions, producing a pump effect in lymphatic flow.…”
Section: Discussionmentioning
confidence: 99%
“…Kinesio taping has been used as an innovative resource in the treatment of lymphedema, as it can drain body fluids. Pivetta et al, 20 reported a significant reduction of lymphedema in groups that used Kinesio taping either alone or in association with other techniques. High-voltage stimulation may increase venous blood flow and edema absorption, since negative polarity has sufficient intensity to provide muscle contractions, producing a pump effect in lymphatic flow.…”
Section: Discussionmentioning
confidence: 99%
“…Kinesio taping has been used as an innovative resource in the treatment of lymphedema, as it can drain body fluids. Pivetta et al 20 reported a significant reduction of lymphedema in groups that used Kinesio taping either alone or in association with other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…O edema se caracteriza pelo acúmulo excessivo de líquido nos espaços extracelulares. Existem duas causas gerais: o vazamento anormal de fluido plasmático para os espaços intersticiais através dos capilares e a incapacidade dos vasos linfáticos de retornar fluido do interstício para o sangue, o que é conhecido por linfedema 3 .…”
Section: Introductionunclassified